Genetic analysis of non-syndromic peg lateralis using whole-exome sequencing - Choi, Junglim; Kim, Sungnam; Ahn, Hyunsoo; Kim, Donghyo; Cho, Sung-Won; Kim, Sanguk; Lee, Jae Hoon (Frontiers in Genetics, 2025)
IntroductionAlthough peg-shaped lateral incisors are a common dental anomaly, the genetic mechanisms governing peg lateralis are poorly understood, particularly in cases where other associated anomalies are absent. Here, we aimed to identify potential candidate genes contributing to the development of non-syndromic peg lateralis via whole-exome sequencing (WES).MethodsSaliva samples were collected from 20 unrelated Korean individuals with non-syndromic peg lateralis. WES was conducted on these samples, and variants with p-value <0.05, false discovery rate <10–10, and odds ratio >1 were filtered. In-silico mutation impact analysis was performed using Polymorphism Phenotyping v2, sorting intolerant from the tolerant, and integrated score of co-evolution and conservation algorithms.ResultsWe identified a heterozygous allele for RP11-131H24.4 and OTOP1, which encodes the otopetrin-1 protein, a proton channel, in all 20 individuals. Gene ontology analysis revealed an association between candidate genes and peg lateralis. We further confirmed that the peg lateralis candidate variants of the same genotype were found in the family members of three individuals.ConclusionThe results suggest a possible function of these newly identified genes in the development of peg lateralis, which remains to be defined. This study may provide new insights into the genetic basis of non-syndromic peg lateralis, establishing a basis for the further analysis of the disease-associated genes identified herein.